Ionospheric Whispers of the Earth's Tremors: Decoding TEC Mysteries in the East Anatolian Fault Zone - Ghafar, Marjan Mohammed; Mohammed, Dawar Hama Khalid; Salh, Hemn; Dleer, Sarkhel; Mukhtar, Sebar; Kulahci, Fatih (Pleiades Publishing Ltd, 2024)
In the evolving field of seismo-ionospheric studies, understanding the variations in the Total Electron Content (TEC) and their implications for seismic forecasting stands paramount. This investigation presents an exhaustive scrutiny of TEC deviations and their prospective role as leading indicators for seismic activities, with a concentrated focus on the tectonically significant East Anatolian Fault Zone. Through the methodical analysis of a 26-day temporal window encapsulating the advent of a notable seismic event, we harnessed advanced statistical approaches to discern and typify TEC aberrations. One of the standout revelations from our research was the unambiguous identification of marked ionospheric TEC irregularities preceding the seismic event. Remarkably, these deviations manifest discernible configurations that, when juxtaposed with geomagnetic storm indices and solar dynamics, suggest their potential utility as seismic harbingers, particularly during epochs typified by serene geomagnetic ambiances. By penetrating these configurations, our inquiry illuminates the complex dynamism intertwining TEC modulations, seismic episodes, and geomagnetic perturbations. Consequently, this exploration augments the contemporary discourse on earthquake-ionosphere dynamics, offering pivotal perspectives that could shape future research trajectories in the domain.
Keywords: Total Electron-Content; Tohoku Earthquake; Solar Euv; Gps Tec; Anomalies; Time